Effect of humic acids on the adsorption of paraquat by goethite - Brigante, Maximiliano Eduardo (2010)
The adsorption of the herbicide paraquat (PQ2+) on goethite and on the binary system humic acid-goethite has been studied in batch experiments by performing adsorption isotherms under different conditions of pH, supporting electrolyte concentration and temperature. The results were completed with capillary electrophoresis (CE) in order to measure the binding isotherm between PQ2+ and humic acid (HA) molecules in solution. PQ2+ adsorption is negligible on the bare goethite surface but important on the HA-goethite adsorbent. In this last case, the adsorption increases by increasing pH and decreasing electrolyte concentration. There are no significant effects of temperature on the adsorption. The adsorption takes place by direct binding of PQ2+ to adsorbed HA molecules leading to the formation of surface species of the type goethite-HA-PQ2+. The results are consistent with a mechanism where PQ2+ binds negatively charged groups of HA (carboxylates and phenolates) forming ionic pairs or outer-sphere complexes. Since goethite in nature usually contains adsorbed HA molecules, it may act as a good adsorbent for cationic herbicides. This will not only benefit the deactivation of the herbicides but also reduce their leaching and transport through groundwater. © 2010 Elsevier B.V.